Pelatihan Dasar Pemrograman Java Keterampilan Hard Skill Bagi Siswa/I SMK Muhammadiyah 2 Palembang - Andreas, Andreas; Kasanova, Sinyo; Robi, Muhammad; Rizky Pribadi, Muhammad (Universitas Multi Data Palembang, Fakultas Ilmu Komputer dan Rekayasa, 2023)
In the era of the digital industry, the role of Information and Communication Technology-based courses is really needed by students as a provision for them to face the changes and demands of the times. SMK acts as a vocational education institution that organizes professional programs such as mechanical engineering, offices, fine arts, catering, administration, and others that can provide skills, one of which is hard skills to support professional skills. In supporting the development of the skills of vocational students in the digital industry era, basic introductory training in the Java programming language is held which aims to introduce the basics and ways of developing or creating software applications.